Control of the magnetic levitation using a PID controller with adaptation based on linear interpolation logic and genetic algorithm - Fila, Dominik; Neumann, Andrzej; Olesik, Bartosz; Pawelec, Jakub; Przybylak, Kamil; Ungier, Mateusz; Wajnert, Dawid (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2025)
This paper presents a magnetic levitation system in which the position of a steel ball is obtained at a desired level by controlling the coil current. The object's behavior was approximated using a mathematical model, considering the inductance's dependence on the ball's position. Then, simulations were carried out in the MATLAB/Simulink environment, and the results were compared with data obtained from a physical bench, confirming the accuracy of the simulation model. As part of the work, two variants of the control system were realized: a classic PID controller and an adaptive version, in which the PID parameters are determined using a genetic algorithm. In addition, linear interpolation logic was introduced, enabling smooth adaptation of the settings depending on the current operating conditions. Experimental tests carried out for step and sinusoidal excitation showed a significant improvement in control quality, reduced rise time, and reduced overshoot in the system using the genetic algorithm and linear interpolation logic compared to a classically tuned PID.